THE ROLE OF EDUCATION AND UPBRINGING IN THE FORMATION OF ECOLOGICAL CONSCIOUSNESS IN EASTERN PHILOSOPHY (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article analyzes the harmony between the concepts of consciousness and beauty (aesthetics) within the framework of Eastern philosophical thought, based on moral and aesthetic values. Drawing on the views of prominent thinkers such as Al-Farabi and Ibn Sina, the study explores the role of consciousness in aesthetic perception, the conscious processes involved in understanding and evaluating beauty, as well as their significance in human education and spiritual development. The article philosophically examines the ethical and aesthetic aspects of perceiving, appreciating, and valuing beauty through consciousness. Furthermore, it reveals the importance of this approach in Eastern philosophy for the formation of contemporary spiritual and moral values.